(untitled) - Shelley, Mary (Đồng Nai, 2009)
One murky night in 1816, on the shores of Lake Geneva, Lord Byron, famed English poet, challenged his friends to a contest--to write a ghost story. The assembled group included the poet Percy Bysshe Shelley; his lover (and future wife) Mary Wollstonecraft Godwin; Mary's stepsister Claire Claremont; and Byron's physician, John William Polidori. The famous result was Mary Shelley's Frankenstein, a work that has retained its hold on the popular imagination for almost two centuries. Less well-known was the curious Polidori's contribution: the first vampire novel. And the
Keywords: English language,Horror stories,Ngôn ngữ tiếng Anh,Truyện kinh dị; Readers,Người thích đọc sách